Relationship between fluid intake, hydration status and cortisol dynamics in healthy, young adult males - Mitchell E. Zaplatosch; Laurie Wideman; Jessica McNeil; Jesse N.L. Sims; William M. Adams (Comprehensive Psychoneuroendocrinology)
Background: Previous studies have identified links between fluid intake, hydration related hormones and cortisol measured at one timepoint but have not considered how hydration may influence cortisol dynamics throughout the day. This study assessed associations between hydration status (copeptin, urinary osmolality, urine volume) and habitual fluid intake with cortisol dynamics. Methods: The day before (DB) a 6-h laboratory visit, 29 male participants (age, 23±4y; BMI, 25.5 ± 4.3 kg/m2; body fat, 17.3 ± 9.3 %) provided 24-h urine samples and a fasted blood sample for hydration status assessment, recorded their 24-h fluid intake for three days prior, and provided 10 saliva samples to assess cortisol dynamics from DB into the evening of the laboratory visit. Calculated indices of cortisol dynamics included: nocturnal cortisol rise (NCR – salivary cortisol rise from bed to awakening), peak salivary cortisol (peak SCORT – highest cortisol of all samples), cortisol awakening response (ΔCAR – difference between high morning sample and awakening sample), area under the curve with respect to ground (AUCG) and increase (AUCI), and diurnal cortisol slope (DCS – rate of change in cortisol from awakening to bed). The relationships between fluid intake or hydration status and cortisol dynamics were analyzed by separating participants into fluid intake tertile groups and by regressing cortisol dynamics on the continuous variables of total fluid intake (TFI) or hydration biomarkers. Results: There were no between-group differences for ΔCAR (p = 0.89), AUCG (p = 0.57), AUCI (p = 0.48), peak SCORT (p = 0.14), NCR (p = 0.95), DCS (p = 0.22), or serum cortisol (p = 0.61). TFI was not associated with log (peak SCORT) (p = 0.49), ΔCAR (p = 0.61), AUCG (p = 0.76), or AUCI (p = 0.56). Copeptin was not associated with log (peak SCORT) (p = 0.99), ΔCAR (p = 0.22), AUCG (p = 0.69) or AUCI (p = 0.18). Urinary hydration markers were not associated with any measures of cortisol dynamics (p > 0.05). These null effects were consistent when controlling for physical activity, sleep, and body fat percentage. Conclusion: In the absence of dehydrating stimuli, measures of fluid intake or hydration status may not be associated with cortisol dynamics in young healthy males.